A collagen composition for brightening skin and preparation method thereof

By combining the immobilized enzyme with the polyethylene glycol-grafted aminated nanocellulose magnetic carrier, the problems of low absorption efficiency and unstable enzyme activity in traditional collagen preparation methods were solved, and efficient and stable fish collagen peptides were achieved. Preparation, enhances the beauty and antioxidant functions of the product.

CN119073594BActive Publication Date: 2025-01-21SHANDONG LONGBEI BIOTECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202411590774.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-21
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Traditional collagen preparation methods have problems such as low absorption efficiency, unstable enzyme activity and insufficient product purity, which limits its wide application in the beauty field.

Method used

By combining the immobilized enzyme with the polyethylene glycol-grafted aminated nanocellulose magnetic carrier, the thermal stability and denaturation resistance of the enzyme are improved, and magnetic separation technology is used to recover the enzyme to ensure the high quality and purity of fish collagen peptides.

Benefits of technology

It achieves the enzyme to maintain activity in a wide temperature and pH range, improves the hydrolysis reaction efficiency, obtains high-purity fish collagen peptides, reduces production costs, and significantly improves the moisturizing, beautifying and antioxidant functions of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119073594B_ABST
    Figure CN119073594B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of oral preparations, and specifically relates to a collagen composition for brightening the skin and a preparation method thereof. The composition of the collagen composition includes the following raw materials by weight: 40 to 60 parts of fish collagen peptides, 2 to 5 parts of arbutin extract, 0.1 to 0.5 parts of black pepper extract, 3 to 6 parts of glutathione, 1 to 3 parts of ellagic acid, 1 to 2 parts of shea butter, 3 to 5 parts of antioxidants, 1 to 2 parts of squalane, 1 to 2 parts of ceramide, 0.5 to 1 part of sodium bicarbonate, 5 to 10 parts of β-cyclodextrin, 1 to 3 parts of lecithin, and 0.5 to 1 part of silicon dioxide. The present invention uses polyethylene glycol grafted amino nanocellulose magnetic carriers to fix enzymes, improve enzyme thermal stability and resistance to denaturation, optimize cross-linking to retain enzyme activity, simplify recovery processes, reduce costs, improve collagen peptide production and quality, and protect active ingredients through nano- and embedding technologies to enhance absorption efficiency and product stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oral preparations, and particularly relates to a collagen composition for brightening skin and a preparation method thereof. Background Art

[0002] Collagen is the most abundant protein in the human body. It is widely found in the skin, bones, tendons and joints, playing a role in supporting and protecting tissues. In the skin, collagen is the main component of the dermis and is responsible for maintaining the elasticity, smoothness and moisture of the skin. As we age, the body's ability to synthesize collagen decreases, leading to signs of aging such as sagging skin, wrinkles, and reduced elasticity. Therefore, supplementing collagen has become an effective way to improve skin aging problems. Dull skin, pigmentation (such as dark spots and freckles) and uneven skin tone are skin problems that many people are concerned about. The main factors that affect skin color include ultraviolet radiation, pollution, stress, unhealthy diet and skin aging, which stimulate the production of melanin, making the skin darker and less shiny. In the beauty industry, whitening and brightening the skin has always been a hot research direction. In addition to topical skin care products, oral beauty products have also received increasing attention in recent years, especially oral preparations that improve skin conditions by regulating body functions internally. Common whitening ingredients include vitamin C, glutathione, coenzyme Q10, hyaluronic acid, etc. These ingredients have antioxidant effects, can inhibit the production of melanin and help brighten the skin tone.

[0003] In recent years, oral collagen supplements have received extensive attention due to their potential anti-aging and skin-beautifying effects. Oral collagen generally exists in the form of collagen peptides. Because the peptide molecules are small, they are more easily absorbed and utilized by the human body. Common sources of collagen include fish skin, pig skin and cow skin. Among them, collagen from fish skin has higher bioavailability. Because of its small molecular weight, it is easier to be absorbed by the skin and has stronger moisturizing and anti-aging effects. Therefore, many collagen compositions that brighten the skin choose to use fish skin collagen peptides as the main ingredient. Studies have shown that oral collagen peptides can be absorbed through the digestive system, promote the synthesis of collagen in the body, and then increase the water content of the skin, improve skin quality, and make the skin smoother, more elastic and shiny. However, the traditional method for preparing collagen has problems such as low absorption efficiency, unstable enzyme activity and insufficient product purity, which limits its wide application in the field of beauty. Therefore, based on the above problems, it is extremely necessary to develop a collagen composition with good biocompatibility and high activity to improve the skin. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a collagen composition for brightening skin and a preparation method thereof.

[0005] The technical effect of the present invention is achieved through the following technical scheme: a collagen composition for brightening the skin, comprising the following raw materials in parts by weight: 40 to 60 parts of fish collagen peptides, 2 to 5 parts of arbutin extract, 0.1 to 0.5 parts of black pepper extract, 3 to 6 parts of glutathione, 1 to 3 parts of ellagic acid, 1 to 2 parts of shea butter, 3 to 5 parts of antioxidants, 1 to 2 parts of squalane, 1 to 2 parts of ceramide, 0.5 to 1 part of sodium bicarbonate, 5 to 10 parts of β-cyclodextrin, 1 to 3 parts of lecithin, and 0.5 to 1 part of silicon dioxide.

[0006] Preferably, the antioxidant is any one of vitamin C, vitamin E and tea polyphenols.

[0007] Preferably, the specific preparation steps of the fish collagen peptide are as follows:

[0008] ①: The fish skin is repeatedly cleaned, soaked in a 0.1M NaOH solution for 2 to 4 hours, and then re-immersed in an acetate buffer solution of pH 3, and left overnight at 4° C. for 12 hours to obtain a pre-treated raw material; the pre-treated raw material is heated in a water bath to 30 to 40° C., treated for 4 to 6 hours, and filtered to obtain a collagen solution;

[0009] ②: Add 1wt% of magnetic nano-immobilized enzyme to the collagen solution prepared in step ①, stir evenly, control the temperature at 37°C, adjust the pH to 7.5, and after the enzymatic reaction for 4 to 8 hours, quickly lower the temperature to 4°C, separate the magnetic nano-immobilized enzyme with a magnetic separator, filter with a 0.22μm filter membrane, centrifuge at 5000rpm for 10min, ultrafilter at 3kDa for 24h, and freeze-dry at -40°C for 24h to obtain fish collagen peptides.

[0010] Preferably, in step ①, the ratio of the amount of the fish skin, the NaOH solution and the acetate buffer is 1 g: 10 mL: 10 mL;

[0011] Preferably, in step ②, the specific preparation steps of the magnetic nano-immobilized enzyme are as follows:

[0012] Ⅰ: Dispersing the modified nanocellulose in deionized water, dispersing it evenly by ultrasonic treatment, and obtaining a modified nanocellulose suspension with a concentration of 1 wt%; adding FeCl3·6H2O and FeCl2·4H2O into the deionized water, stirring and mixing evenly, and obtaining an iron salt mixed solution;

[0013] Ⅱ: In a nitrogen atmosphere, slowly add the iron salt mixed solution prepared in step Ⅰ to the modified nanocellulose suspension prepared in step Ⅰ, stir and mix evenly, heat to raise the temperature to 60-70°C, slowly add ammonia water to adjust the pH to 10, and then stir and react at a speed of 1000-1500 rpm for 1-2 hours. After the reaction is completed, cool to room temperature, centrifuge, take the precipitate, wash with deionized water until the pH is neutral, and vacuum dry at 40-60°C to constant weight to obtain magnetic nanofibers;

[0014] III: adding collagenase and trypsin to a pH 7 phosphate buffer, stirring and mixing evenly to obtain an enzyme solution; adding the magnetic nanofibers prepared in step II to a 0.25-0.5wt% glutaraldehyde solution, heating in a water bath to increase the temperature to 30-35°C, gently stirring for 1-2h, and washing three times with a pH 7 phosphate buffer to obtain activated magnetic nanofibers;

[0015] IV: Add the activated magnetic nanofibers prepared in step III to the enzyme solution, add 0.6-1% trehalose, and react with slight stirring at 4°C for 6-8h. Then use a magnet to separate the magnetic nanofibers after immobilizing the enzyme, wash them three times with pH 7 phosphate buffer, and vacuum freeze-dry at -20°C to constant weight to obtain magnetic nano-immobilized enzyme.

[0016] Preferably, in step I, the specific preparation steps of the modified nanocellulose are as follows:

[0017] (1): Nanocellulose was dispersed in anhydrous ethanol and ultrasonically treated for 30 min to obtain a 1 wt% nanocellulose dispersion; 2 wt% APTES was slowly added to the nanocellulose dispersion under a nitrogen atmosphere, 1% of the total volume of 1 M ammonia was added, heated to 40-60° C. in a water bath and stirred for 3-6 h, centrifuged at 8000 rpm for 10 min, washed with anhydrous ethanol for 5 times, and dried at 50° C. to constant weight to obtain amino nanofibers;

[0018] (2): dissolving PEG-COOH in 50 wt% ethanol, stirring to dissolve evenly, adding EDC and NHS, stirring to react for 15 to 30 min, and obtaining an activated PEG-COOH solution; dispersing the amino nanofibers prepared in step (1) in 0.1 M PBS buffer to obtain a 2 wt% amino nanofiber solution;

[0019] (3): Slowly add the activated PEG-COOH solution prepared in step (2) to the amino nanofiber solution, control the pH to 6-6.8, stir the reaction in an ice bath for 1-2 hours, centrifuge at 8000 rpm for 10 minutes, wash with ethanol repeatedly for 5 times, and dry at 60°C to constant weight to obtain modified nanocellulose.

[0020] Preferably, in step I, the ratio of the amount of FeCl3·6H2O, FeCl2·4H2O and deionized water is 1.8-2g:1g:50-100mL;

[0021] Preferably, in step II, the volume ratio of the iron salt mixed solution to the modified nanocellulose suspension is 1:1-2;

[0022] Preferably, in step III, the ratio of the amount of collagenase, trypsin and phosphate buffer is 6 mg:4 mg:5 mL; the activity of the collagenase is 1500 U / g; the activity of the trypsin is 4500 U / g;

[0023] Preferably, in step IV, the ratio of the amount of the activated magnetic nanofiber to the enzyme solution is 1 g:100 mL;

[0024] Preferably, in step (2), the ratio of the amount of PEG-COOH, EDC, NHS and 50wt% ethanol is 20g:2-2.3g:1.3-1.4g:200mL;

[0025] Preferably, in step (3), the volume ratio of the activated PEG-COOH solution to the amino nanofiber solution is 1.5 to 2:2.

[0026] Preferably, another aspect of the present invention is to provide a method for preparing a collagen composition for brightening skin, and the specific preparation steps are as follows:

[0027] S1: dissolving arbutin extract, glutathione, ellagic acid, antioxidants and black pepper extract in distilled water, stirring until completely dissolved, adjusting the pH to 6.5-7, and obtaining an aqueous phase; adding shea butter, squalane and ceramide to a 70wt% ethanol solution, heating the solution to 40°C in a water bath, stirring to completely dissolve, and then adding lecithin, continuing to stir to form a uniform oil phase;

[0028] S2: slowly adding the oil phase prepared in step S1 to the water phase, controlling the temperature to 4°C in an ice bath, and stirring at 10000 rpm for 15 min to obtain a primary emulsion; subjecting the primary emulsion to ultrasonic treatment at 400 W for 20 min in an ice bath, and then subjecting the homogenizer to a cycle treatment at 800 bar pressure for 3 times to obtain a nanoemulsion;

[0029] S3: adding β-cyclodextrin to the nanoemulsion prepared in step S2, stirring and reacting at room temperature for 2 hours, and then vacuum rotary evaporating at 40°C for 2-4 hours to obtain an embedded emulsion; treating the embedded emulsion with a spray dryer, setting the inlet temperature to 80°C and the outlet temperature to 40-50°C to obtain a nano-embedded powder;

[0030] S4: Stir the nano-embedded powder prepared in step S3, fish collagen peptide, sodium bicarbonate and silicon dioxide for 30 minutes to mix evenly to obtain a collagen composition.

[0031] The beneficial effects of the present invention are as follows:

[0032] The present invention combines the immobilized enzyme with the aminated nanocellulose magnetic carrier grafted with polyethylene glycol, effectively improves the thermal stability and anti-denaturation of the enzyme in the process of hydrolyzing fish collagen, enables the enzyme to maintain activity in a wide range of temperature and pH, ensures the efficient hydrolysis reaction, and at the same time, by optimizing the concentration of the cross-linking agent, maximizes the activity of the enzyme, ensures that the fish collagen is fully hydrolyzed to generate high-quality collagen peptides. The magnetic nanocarrier enables the enzyme to be quickly recovered from the reaction system by magnetic separation technology, avoids the traditional centrifugation or filtration steps, simplifies the operation process and reduces the physical damage to the collagen peptide. This effective magnetic separation reduces the residue of the enzyme carrier and the unreacted enzyme, ensures that the fish collagen peptide finally obtained has a higher purity and meets the food or pharmaceutical grade standards. The high dispersibility and stability of the immobilized enzyme ensure that the enzyme molecule is fully in contact with the fish collagen substrate, significantly improves the efficiency of the hydrolysis reaction, and thus obtains a higher yield of collagen peptides under the same conditions. In addition, the enzyme can be recycled and used multiple times, and can still maintain a high hydrolysis efficiency under reasonable operating conditions, significantly reducing the production cost. The polyethylene glycol-grafted amino nanocellulose carrier has good biocompatibility and stability. The polyethylene glycol chain forms a hydration layer on the carrier surface to prevent the denaturation and inactivation of the enzyme, and effectively avoids the physical aggregation and degradation of nanocellulose that may occur during the hydrolysis process. In addition, the amino treatment provides abundant active sites to ensure the stable immobilization of the enzyme. The nanoscale magnetic particles are embedded in the nanocellulose, avoiding direct contact with the enzyme active center and protecting the activity of the enzyme. The high specific surface area and rich pore structure of the nanocellulose carrier provide a large number of active sites for the immobilization of the enzyme, promoting the diffusion of the substrate and the efficient action of the enzyme. The grafting of polyethylene glycol improves the hydrophilicity and dispersibility of the carrier, prevents the aggregation of the carrier, and further increases the contact probability between the enzyme and the substrate. This immobilization and magnetic recovery technology not only improves the efficiency of enzyme use, reduces enzyme consumption, and significantly reduces production costs, but also ensures the excellent functionality of collagen peptides in moisturizing, beauty and anti-oxidation, and can effectively prepare high-quality oral collagen preparations.

[0033] The present invention adjusts the gastric acid environment by adding a small amount of sodium bicarbonate to improve the absorption efficiency of collagen and glutathione; at the same time, piperine in black pepper extract can enhance the absorption effect of certain active ingredients (such as glutathione), promote the absorption of nutrients in the gastrointestinal tract, and combine nano- and embedding technologies to effectively protect active ingredients that are easily oxidized, easily degraded or easily inactivated, not only extending the shelf life of the product, but also ensuring the stability of these ingredients in the gastrointestinal tract, preventing them from being destroyed by gastric acid and enzymes, ensuring smooth absorption, and nano-technology reduces the particle size of the active ingredients to the nanometer level, significantly increasing the surface area, thereby improving solubility and absorption efficiency. For products in the form of oral powders, nano-technology can effectively promote the uniform dispersion of water-soluble and fat-soluble components and accelerate their absorption in the intestine. After nano-sizing, the absorption efficiency of these active ingredients is improved. At the same time, the encapsulation technology helps to prolong their action time in the digestive tract and to a certain extent reduce their decomposition by gastric acid and digestive enzymes. In addition, nano-sizing and encapsulation technology ensure that multiple active ingredients can be evenly mixed to form a synergistic effect, effectively improving the effect of fish collagen on skin whitening, repairing and restoring elasticity. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 This is a test diagram of the antioxidant performance of fish collagen peptides prepared in Example 2 of the present invention and Comparative Examples 1 and 2;

[0036] Figure 2 It is a test chart of the antioxidant performance of the collagen compositions prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3;

[0037] Figure 3 It is a graph showing the in vitro performance test results of the collagen compositions prepared in Examples 1 to 3 of the present invention;

[0038] Figure 4 3 is a graph showing the moisturizing performance test results of the collagen compositions prepared in Example 2 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.

[0040] Example 1: A collagen composition for brightening the skin, comprising the following raw materials in parts by weight: 40 parts of fish collagen peptide, 2 parts of arbutin extract, 0.1 parts of black pepper extract, 3 parts of glutathione, 1 part of ellagic acid, 1 part of shea butter, 3 parts of antioxidants, 1 part of squalane, 1 part of ceramide, 0.5 parts of sodium bicarbonate, 5 parts of β-cyclodextrin, 1 part of lecithin, and 0.5 parts of silicon dioxide.

[0041] The specific preparation steps of fish collagen peptide are as follows:

[0042] ①: 50 g of fish skin was repeatedly cleaned, soaked in 500 mL of 0.1 M NaOH solution for 2 h, and then re-immersed in 500 mL of pH 3 acetate buffer, and kept at 4 ° C overnight for 12 h to obtain a pre-treated raw material; the pre-treated raw material was heated in a water bath to 30 ° C, treated for 6 h, and filtered to obtain a collagen solution;

[0043] ②: Add 5 g of magnetic nano-immobilized enzyme to 500 mL of collagen solution prepared in step ①, stir evenly, control the temperature at 37 ° C, adjust the pH to 7.5, and after 4 hours of enzymatic reaction, quickly lower the temperature to 4 ° C, separate the magnetic nano-immobilized enzyme with a magnetic separator, filter with a 0.22 μm filter membrane, centrifuge at 5000 rpm for 10 min, ultrafilter at 3 kDa for 24 hours, and freeze-dry at -40 ° C for 24 hours to obtain fish collagen peptides.

[0044] The specific preparation steps of magnetic nano-immobilized enzyme are as follows:

[0045] Ⅰ: Disperse 10 g of modified nanocellulose in deionized water, disperse evenly by ultrasonic treatment, and obtain a modified nanocellulose suspension with a concentration of 1 wt%; add 18 g of FeCl3·6H2O and 10 g of FeCl2·4H2O into 500 mL of deionized water, stir and mix evenly, and obtain an iron salt mixed solution;

[0046] Ⅱ: In a nitrogen atmosphere, 500 mL of the iron salt mixed solution prepared in step Ⅰ was slowly added to 1000 mL of the modified nanocellulose suspension prepared in step Ⅰ, stirred and mixed evenly, heated to 60°C, slowly added ammonia water to adjust the pH to 10, and then stirred at 1000 rpm for 2 hours. After the reaction was completed, it was cooled to room temperature, centrifuged, and the precipitate was taken, washed with deionized water until the pH was neutral, and vacuum dried at 40°C to constant weight to obtain magnetic nanofibers;

[0047] III: Add 0.6 g collagenase and 0.4 g trypsin to 500 mL of pH 7 phosphate buffer, stir and mix evenly to obtain an enzyme solution; add 5 g of the magnetic nanofibers prepared in step II to 100 mL of 0.25 wt% glutaraldehyde solution, heat in a water bath to increase the temperature to 30°C, stir gently for 2 h, and wash three times with pH 7 phosphate buffer to obtain activated magnetic nanofibers;

[0048] IV: Add 5 g of activated magnetic nanofibers prepared in step III to 500 mL of enzyme solution, add 3 g of trehalose, and react with slight stirring at 4°C for 6 h. Then use a magnet to separate the magnetic nanofibers with immobilized enzymes, wash them three times with pH 7 phosphate buffer, and vacuum freeze-dry at -20°C to constant weight to obtain magnetic nano-immobilized enzymes.

[0049] The specific preparation steps of modified nanocellulose are as follows:

[0050] (1): 10 g of nanocellulose was dispersed in anhydrous ethanol and ultrasonically treated for 30 min to obtain a 1 wt% nanocellulose dispersion; under a nitrogen atmosphere, 0.2 g of APTES was slowly added to 1000 mL of the nanocellulose dispersion, 10 mL of 1 M ammonia was added, the mixture was heated to 40 °C in a water bath and stirred for 6 h, centrifuged at 8000 rpm for 10 min, washed with anhydrous ethanol for 5 times, and dried at 50 °C to constant weight to obtain amino nanofibers;

[0051] (2): Dissolve 20 g of PEG-COOH in 200 mL of 50 wt% ethanol, stir to dissolve evenly, add 2 g of EDC and 1.3 g of NHS, stir to react for 15 min, and obtain an activated PEG-COOH solution; disperse the amino nanofibers prepared in step (1) in 0.1 M PBS buffer to obtain a 2 wt% amino nanofiber solution;

[0052] (3): 150 mL of the activated PEG-COOH solution prepared in step (2) was slowly added dropwise to 200 mL of the amino-modified nanofiber solution, the pH was controlled to 6, the mixture was stirred for reaction for 1 h in an ice bath, centrifuged at 8000 rpm for 10 min, washed with ethanol for 5 times, and dried at 60° C. to constant weight to obtain modified nanocellulose;

[0053] The specific preparation steps of the collagen composition are as follows:

[0054] S1: dissolving arbutin extract, glutathione, ellagic acid, antioxidants and black pepper extract in distilled water, stirring until completely dissolved, adjusting the pH to 6.5, and obtaining an aqueous phase; adding shea butter, squalane and ceramide to a 70wt% ethanol solution, heating the solution to 40°C in a water bath, stirring to completely dissolve, and then adding lecithin, continuing to stir to form a uniform oil phase;

[0055] S2: slowly adding the oil phase prepared in step S1 to the water phase, controlling the temperature to 4°C in an ice bath, and stirring at 10000 rpm for 15 min to obtain a primary emulsion; subjecting the primary emulsion to ultrasonic treatment at 400 W for 20 min in an ice bath, and then subjecting the homogenizer to a cycle treatment at 800 bar pressure for 3 times to obtain a nanoemulsion;

[0056] S3: adding β-cyclodextrin to the nanoemulsion prepared in step S2, stirring and reacting at room temperature for 2 hours, and then vacuum rotary evaporating at 40°C for 2 hours to obtain an embedded emulsion; treating the embedded emulsion with a spray dryer, setting the inlet temperature to 80°C and the outlet temperature to 40°C to obtain a nano-embedded powder;

[0057] S4: Stir the nano-embedded powder prepared in step S3, fish collagen peptide, sodium bicarbonate and silicon dioxide for 30 minutes to mix evenly to obtain a collagen composition.

[0058] Example 2: A collagen composition for brightening the skin, comprising the following raw materials in parts by weight: 60 parts of fish collagen peptide, 4 parts of arbutin extract, 0.4 parts of black pepper extract, 5 parts of glutathione, 2 parts of ellagic acid, 2 parts of shea butter, 4 parts of antioxidants, 2 parts of squalane, 1.5 parts of ceramide, 0.6 parts of sodium bicarbonate, 8 parts of β-cyclodextrin, 2 parts of lecithin, and 0.6 parts of silicon dioxide.

[0059] The specific preparation steps of fish collagen peptide are as follows:

[0060] ①: 50 g of fish skin was repeatedly cleaned, soaked in 500 mL of 0.1 M NaOH solution for 3 h, and then re-immersed in 500 mL of pH 3 acetate buffer, at 4 ° C overnight for 12 h to obtain a pre-treated raw material; the pre-treated raw material was heated in a water bath to 35 ° C, treated for 5 h, and filtered to obtain a collagen solution;

[0061] ②: Add 5 g of magnetic nano-immobilized enzyme to 500 mL of collagen solution prepared in step ①, stir evenly, control the temperature at 37 ° C, adjust the pH to 7.5, and after 6 hours of enzymatic reaction, quickly lower the temperature to 4 ° C, separate the magnetic nano-immobilized enzyme with a magnetic separator, filter with a 0.22 μm filter membrane, centrifuge at 5000 rpm for 10 min, ultrafilter at 3 kDa for 24 hours, and freeze-dry at -40 ° C for 24 hours to obtain fish collagen peptides.

[0062] The specific preparation steps of magnetic nano-immobilized enzyme are as follows:

[0063] Ⅰ: Disperse 10 g of modified nanocellulose in deionized water, disperse evenly by ultrasonic treatment, and obtain a modified nanocellulose suspension with a concentration of 1 wt%; add 20 g of FeCl3·6H2O and 10 g of FeCl2·4H2O into 1000 mL of deionized water, stir and mix evenly, and obtain an iron salt mixed solution;

[0064] Ⅱ: In a nitrogen atmosphere, slowly add 1000mL of the iron salt mixed solution prepared in step Ⅰ to 1000mL of the modified nanocellulose suspension prepared in step Ⅰ, stir and mix evenly, heat to 65°C, slowly add ammonia water to adjust the pH to 10, then stir and react at a speed of 1200rpm for 2h. After the reaction is completed, cool to room temperature, centrifuge, take the precipitate, wash with deionized water until the pH is neutral, and vacuum dry at 50°C to constant weight to obtain magnetic nanofibers;

[0065] III: Add 0.6 g collagenase and 0.4 g trypsin to 500 mL of pH 7 phosphate buffer, stir and mix evenly to obtain an enzyme solution; add 5 g of magnetic nanofibers prepared in step II to 100 mL of 0.5 wt% glutaraldehyde solution, heat in a water bath to raise the temperature to 32°C, stir gently for 2 h, and wash three times with pH 7 phosphate buffer to obtain activated magnetic nanofibers;

[0066] IV: Add 5 g of activated magnetic nanofibers prepared in step III to 500 mL of enzyme solution, add 5 g of trehalose, and react with slight stirring at 4°C for 8 h. Then use a magnet to separate the magnetic nanofibers after immobilizing the enzyme, wash them three times with pH 7 phosphate buffer, and vacuum freeze-dry them at -20°C to constant weight to obtain magnetic nano-immobilized enzyme.

[0067] The specific preparation steps of modified nanocellulose are as follows:

[0068] (1): 10 g of nanocellulose was dispersed in anhydrous ethanol and ultrasonically treated for 30 min to obtain a 1 wt% nanocellulose dispersion; under a nitrogen atmosphere, 0.2 g of APTES was slowly added to 1000 mL of the nanocellulose dispersion, 10 mL of 1 M ammonia was added, the mixture was heated to 50 °C in a water bath and stirred for 5 h, centrifuged at 8000 rpm for 10 min, washed with anhydrous ethanol for 5 times, and dried at 50 °C to constant weight to obtain amino nanofibers;

[0069] (2): Dissolve 20 g of PEG-COOH in 200 mL of 50 wt% ethanol, stir to dissolve evenly, add 2.3 g of EDC and 1.4 g of NHS, stir to react for 25 min, and obtain an activated PEG-COOH solution; disperse the amino nanofibers prepared in step (1) in 0.1 M PBS buffer to obtain a 2 wt% amino nanofiber solution;

[0070] (3): 200 mL of the activated PEG-COOH solution prepared in step (2) was slowly added dropwise to 200 mL of the amino-modified nanofiber solution, the pH was controlled to 6.5, the mixture was stirred for reaction for 2 h in an ice bath, centrifuged at 8000 rpm for 10 min, washed with ethanol for 5 times, and dried at 60° C. to constant weight to obtain modified nanocellulose;

[0071] The specific preparation steps of the collagen composition are as follows:

[0072] S1: dissolving arbutin extract, glutathione, ellagic acid, antioxidants and black pepper extract in distilled water, stirring until completely dissolved, adjusting the pH to 7, and obtaining an aqueous phase; adding shea butter, squalane and ceramide to a 70wt% ethanol solution, heating the solution to 40°C in a water bath, stirring to completely dissolve, and then adding lecithin, continuing to stir, and forming a uniform oil phase;

[0073] S2: slowly adding the oil phase prepared in step S1 to the water phase, controlling the temperature to 4°C in an ice bath, and stirring at 10000 rpm for 15 min to obtain a primary emulsion; subjecting the primary emulsion to ultrasonic treatment at 400 W for 20 min in an ice bath, and then subjecting the homogenizer to a cycle treatment at 800 bar pressure for 3 times to obtain a nanoemulsion;

[0074] S3: adding β-cyclodextrin to the nanoemulsion prepared in step S2, stirring and reacting at room temperature for 2 hours, and then vacuum rotary evaporating at 40°C for 3 hours to obtain an embedded emulsion; treating the embedded emulsion with a spray dryer, setting the inlet temperature to 80°C and the outlet temperature to 45°C to obtain a nano-embedded powder;

[0075] S4: Stir the nano-embedded powder prepared in step S3, fish collagen peptide, sodium bicarbonate and silicon dioxide for 30 minutes to mix evenly to obtain a collagen composition.

[0076] Example 3: A collagen composition for brightening the skin, comprising the following raw materials in parts by weight: 50 parts of fish collagen peptide, 5 parts of arbutin extract, 0.5 parts of black pepper extract, 6 parts of glutathione, 3 parts of ellagic acid, 2 parts of shea butter, 5 parts of antioxidants, 1.5 parts of squalane, 2 parts of ceramide, 1 part of sodium bicarbonate, 10 parts of β-cyclodextrin, 3 parts of lecithin, and 1 part of silicon dioxide.

[0077] The specific preparation steps of fish collagen peptide are as follows:

[0078] ①: 50 g of fish skin was repeatedly cleaned, soaked in 500 mL of 0.1 M NaOH solution for 4 h, and then re-immersed in 500 mL of pH 3 acetate buffer, at 4 ° C overnight for 12 h to obtain a pre-treated raw material; the pre-treated raw material was heated in a water bath to 40 ° C, treated for 4 h, and filtered to obtain a collagen solution;

[0079] ②: Add 5 g of magnetic nano-immobilized enzyme to 500 mL of collagen solution prepared in step ①, stir evenly, control the temperature at 37 ° C, adjust the pH to 7.5, and after 8 hours of enzymatic reaction, quickly lower the temperature to 4 ° C, separate the magnetic nano-immobilized enzyme with a magnetic separator, filter with a 0.22 μm filter membrane, centrifuge at 5000 rpm for 10 min, ultrafilter at 3 kDa for 24 hours, and freeze-dry at -40 ° C for 24 hours to obtain fish collagen peptides.

[0080] The specific preparation steps of magnetic nano-immobilized enzyme are as follows:

[0081] Ⅰ: Disperse 10 g of modified nanocellulose in deionized water, disperse evenly by ultrasonic treatment, and obtain a modified nanocellulose suspension with a concentration of 1 wt%; add 19 g of FeCl3·6H2O and 10 g of FeCl2·4H2O into 800 mL of deionized water, stir and mix evenly, and obtain an iron salt mixed solution;

[0082] Ⅱ: In a nitrogen atmosphere, 800 mL of the iron salt mixed solution prepared in step Ⅰ was slowly added to 1000 mL of the modified nanocellulose suspension prepared in step Ⅰ, and the mixture was stirred and mixed evenly. The temperature was raised to 70°C, and ammonia water was slowly added dropwise to adjust the pH to 10. Then, the mixture was stirred at 1500 rpm for 1 hour. After the reaction was completed, the mixture was cooled to room temperature, centrifuged, and the precipitate was taken. The mixture was washed with deionized water until the pH was neutral, and vacuum dried at 60°C to constant weight to obtain magnetic nanofibers.

[0083] III: Add 0.6 g collagenase and 0.4 g trypsin to 500 mL of pH 7 phosphate buffer, stir and mix evenly to obtain an enzyme solution; add 5 g of the magnetic nanofibers prepared in step II to 100 mL of 0.4 wt% glutaraldehyde solution, heat in a water bath to raise the temperature to 35°C, stir gently for 1 hour, and wash three times with pH 7 phosphate buffer to obtain activated magnetic nanofibers;

[0084] IV: Add 5 g of activated magnetic nanofibers prepared in step III to 500 mL of enzyme solution, add 4 g of trehalose, and react with slight stirring at 4°C for 8 h. Then use a magnet to separate the magnetic nanofibers with immobilized enzymes, wash them three times with pH 7 phosphate buffer, and vacuum freeze-dry them at -20°C to constant weight to obtain magnetic nano-immobilized enzymes.

[0085] The specific preparation steps of modified nanocellulose are as follows:

[0086] (1): 10 g of nanocellulose was dispersed in anhydrous ethanol and ultrasonically treated for 30 min to obtain a 1 wt% nanocellulose dispersion; under a nitrogen atmosphere, 0.2 g of APTES was slowly added to the nanocellulose dispersion, 10 mL of 1 M ammonia was added, the mixture was heated to 60 ° C in a water bath and stirred for 3 h, centrifuged at 8000 rpm for 10 min, washed with anhydrous ethanol for 5 times, and dried at 50 ° C to constant weight to obtain amino nanofibers;

[0087] (2): Dissolve 20 g of PEG-COOH in 200 mL of 50 wt% ethanol, stir to dissolve evenly, add 2.2 g of EDC and 1.38 g of NHS, stir to react for 30 min, and obtain an activated PEG-COOH solution; disperse the amino nanofibers prepared in step (1) in 0.1 M PBS buffer to obtain a 2 wt% amino nanofiber solution;

[0088] (3): 200 mL of the activated PEG-COOH solution prepared in step (2) was slowly added dropwise to 200 mL of the amino-modified nanofiber solution, the pH was controlled to 6.8, the mixture was stirred for reaction for 2 h in an ice bath, centrifuged at 8000 rpm for 10 min, washed with ethanol for 5 times, and dried at 60° C. to constant weight to obtain modified nanocellulose;

[0089] The specific preparation steps of the collagen composition are as follows:

[0090] S1: dissolving arbutin extract, glutathione, ellagic acid, antioxidants and black pepper extract in distilled water, stirring until completely dissolved, adjusting the pH to 6.8, and obtaining an aqueous phase; adding shea butter, squalane and ceramide to a 70wt% ethanol solution, heating the solution to 40°C in a water bath, stirring to completely dissolve, and then adding lecithin, continuing to stir, and forming a uniform oil phase;

[0091] S2: slowly adding the oil phase prepared in step S1 to the water phase, controlling the temperature to 4°C in an ice bath, and stirring at 10000 rpm for 15 min to obtain a primary emulsion; subjecting the primary emulsion to ultrasonic treatment at 400 W for 20 min in an ice bath, and then subjecting the homogenizer to a cycle treatment at 800 bar pressure for 3 times to obtain a nanoemulsion;

[0092] S3: adding β-cyclodextrin to the nanoemulsion prepared in step S2, stirring and reacting at room temperature for 2 hours, and then vacuum rotary evaporating at 40°C for 4 hours to obtain an embedded emulsion; treating the embedded emulsion with a spray dryer, setting the inlet temperature to 80°C and the outlet temperature to 50°C to obtain a nano-embedded powder;

[0093] S4: Stir the nano-embedded powder prepared in step S3, fish collagen peptide, sodium bicarbonate and silicon dioxide for 30 minutes to mix evenly to obtain a collagen composition.

[0094] Comparative Example 1: The operation of Comparative Example 1 is basically the same as that of Example 2, except that collagenase and trypsin are used to directly replace the magnetic nano-immobilized enzyme hydrolysis to prepare fish collagen peptides in Comparative Example 1.

[0095] Comparative Example 2: The operation of Comparative Example 2 is basically the same as that of Example 2, except that in Comparative Example 2, magnetic nano-immobilized enzyme without polyethylene glycol grafting is used to replace magnetic nano-immobilized enzyme for hydrolysis to prepare fish collagen peptide.

[0096] Comparative Example 3: The operation of Comparative Example 3 is basically the same as that of Example 2, except that in Comparative Example 3, all raw materials are directly mixed and then freeze-spray-dried to prepare the collagen composition.

[0097] Performance Test:

[0098] Enzyme thermal stability and pH stability test: The magnetic nano-immobilized enzymes prepared in Example 2 and Comparative Example 2 and the free enzymes (collagenase and trypsin) in the control group were dissolved in PBS buffer at pH 7, respectively, to ensure that the enzyme concentration was consistent (100U / mL), and the two enzyme solutions were respectively divided into different test tubes, and each group was subjected to the following temperature test (30°C, 50°C, 70°C), and each temperature setting was repeated 3 times. At 0 minutes, 30 minutes, 60 minutes, 90 minutes, and 120 minutes, a portion of the enzyme solution was taken out for enzyme activity test, and the same amount of substrate (gelatin solution) was added to the enzyme solution taken out at each time point, and the reaction was carried out at an appropriate temperature of 37°C for 30 minutes. After stopping the reaction, the enzyme activity was detected by colorimetry, and the enzyme activity before heating was taken as 100%, and the residual enzyme activity was calculated. The thermal stability results are shown in Table 1;

[0099] The magnetic nano-immobilized enzymes prepared in Example 2 and Comparative Example 2 and the free enzymes (collagenase and trypsin) in the control group were dissolved in PBS buffers of pH 3.5, pH 5.5, pH 7.5 and pH 9.5 to ensure that the enzyme concentration was consistent (100 U / mL). Each group of tests was repeated 3 times. After treatment at 37° C. for 1 hour, the treated enzyme solution was taken, and the substrate solution (gelatin solution) was added. The reaction was carried out at an appropriate temperature of 37° C. for 30 minutes. After the reaction, the reaction was stopped, and the hydrolysis product was detected by colorimetry to determine the residual enzyme activity. The enzyme activity under each pH condition was calculated with the untreated enzyme activity under pH 7 as 100%. The results are shown in Table 2.

[0100] Table 1. Enzyme thermal stability test results

[0101]

[0102] Table 2. Enzyme pH stability test results

[0103]

[0104] It can be seen from the results of Table 1 and Table 2 above that the magnetic nano-immobilized enzyme prepared by the present invention exhibits stability and activity superior to that of the free enzyme under both acidic and alkaline conditions, and the solidification effect enhances the tolerance of the enzyme to extreme pH; the activity of the free enzyme decreases significantly under non-optimal pH conditions; the enzyme activity of the magnetic nano-immobilized enzyme at different temperatures shows obvious advantages, especially under high temperature (50°C and 70°C) conditions, the thermal stability of the immobilized enzyme enables it to maintain a high activity, while the free enzyme is rapidly inactivated; from the results of Comparative Example 1 and Example 2, it can be seen that the polyethylene glycol grafting effectively forms a protective hydration layer on the enzyme surface, reduces the conformational changes caused by heat, and protects the active center of the enzyme. In addition, the inoculation of polyethylene glycol may also effectively reduce the interaction and aggregation between enzyme molecules to a certain extent, and maintain the activity of the enzyme; from the results of Comparative Example 2 and Example 2, it can be seen that under the optimum pH conditions, the enzyme activity of the magnetic nano-immobilized enzyme after polyethylene glycol grafting is more significantly improved, which may be because the grafting of polyethylene glycol effectively improves the conformational stability of the enzyme.

[0105] Antioxidant test: Take 2mL DPPH solution and 2mL of the sample solution to be tested (0.1g of the fish collagen peptide prepared in Example 2 and Comparative Examples 1 and 2 are respectively dissolved in 5mL of anhydrous ethanol; 0.1g of the collagen composition prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are respectively dissolved in 5mL of anhydrous ethanol), mix well, place in a dark place for 30 minutes, and measure the absorbance at 517nm with anhydrous ethanol solution as a reference. The DPPH solution is a solution with a concentration of 0.1mM prepared with anhydrous ethanol as the solvent. Calculate the DPPH free radical scavenging rate (scavenging rate = [1-(absorbance of the mixture of sample and DPPH-absorbance of the sample solution without DPPH / absorbance of the solution containing only DPPH] × 100%), repeat the test 3 times, and take the average value. The antioxidant results of fish collagen peptides are as follows: Figure 1 As shown, the antioxidant properties of collagen compositions are Figure 2 shown.

[0106] By the above Figure 1 The results show that the magnetic nano-immobilized enzyme prepared by the present invention can efficiently hydrolyze and prepare fish collagen peptides, and the fish collagen peptides with better efficiency are obtained compared with conventional enzyme hydrolysis; from the results of Example 2 and Comparative Example 1, it can be seen that the fish collagen peptides prepared by magnetic nano-immobilized enzyme hydrolysis have better antioxidant properties; from the results of Example 2 and Comparative Example 2, it can be seen that the lack of polyethylene glycol grafting may lead to physical aggregation and degradation of nanocellulose, and the enzymatic hydrolysis performance is affected. At the same time, due to the lack of polyethylene glycol chain protection, the enzyme activity is affected, which leads to a decrease in the antioxidant properties of the extracted fish collagen peptides.

[0107] By the above Figure 2The results show that the collagen composition prepared by the present invention has excellent antioxidant properties. From the results of Example 2 and Comparative Example 3, it can be seen that the collagen composition prepared by nano-sizing and encapsulation technology not only protects the stability of the active ingredients and prevents their degradation, but also improves their solubility and bioavailability, so that the antioxidant activity can be fully exerted.

[0108] Biocompatibility testing:

[0109] In vitro test: The collagen compositions prepared in Examples 1 to 3 and the control group (DMEM culture medium) were evenly distributed in a 96-well plate with 16 wells per group of samples, and then the HaCaT epithelial cells were diluted to 1×10 5 After 50 μL of the sample was added, 8 wells without sample were inoculated into a 96-well plate. Meanwhile, 8 wells without sample were used as negative control group, and 8 wells with 10 wt % dimethyl sulfoxide solution added were used as positive control group. The temperature was set at 37°C and CO2 concentration was 5%. After 24 h of incubation, 20 μL of 5 mg / mL MTT solution was added. The incubation was continued for 4 h. The culture medium in the wells was aspirated, and 100 μL of dimethyl sulfoxide was added to the wells. The absorbance (OD value) was measured at 490 nm using a microplate reader, and the relative survival rate of the cells was measured [cell survival rate (%) = (OD value of the embodiment - OD value of the negative control group) / (OD value of the positive control group - OD value of the negative control group) × 100%]. The results are shown in FIG. Figure 3 shown.

[0110] Depend on Figure 3 The results show that the collagen composition prepared by the present invention has no significant effect on cell activity, no significant toxic effect on cells, and has excellent biocompatibility.

[0111] Oral toxicity test: According to the national standard GB 15193.3-2014, 30 mice weighing about 20 g, 15 females and 15 males, were selected and evenly divided into three groups. They were raised at 25°C, 60% humidity, and 12 h light / 12 h dark. The collagen peptide prepared in Example 2 was administered at a dose of 200 mg / kg and 1000 mg / kg, and the control group was administered with the same dose of normal saline. After 1 hour of administration, the behavioral changes of the animals were observed and recorded. The animals were weighed before administration and on the first, 7, and 14 days after administration, and the weight changes were recorded. The weight change after administration was calculated based on the weight before administration as the baseline = (weight after administration - weight before administration) / weight before administration × 100%. The results were averaged, and the abnormal reactions and whether death occurred were recorded. The results are shown in Table 3.

[0112] Table 3. Results of oral toxicity test in mice

[0113]

[0114] From the results in Table 3 above, it can be seen that the fish collagen peptides prepared by the magnetic nano-immobilized enzyme prepared by the present invention will not have obvious negative effects on mice when used at normal doses. The fish collagen peptides prepared by magnetic nano-immobilized enzyme hydrolysis are safe and effective. When used at higher doses, the reduction in diet on the 7th day may be due to gastrointestinal discomfort caused by excessively high content of active ingredients.

[0115] Moisturizing performance test: Based on the above biocompatibility test, 60 healthy female volunteers with no history of allergy to skin care products were selected. The volunteers were aged between 25 and 35 years old and were randomly divided into test groups 1 to 2 and a control group. The test groups took the collagen compositions prepared in Example 2 and Comparative Example 1 orally, and the control group took glucose powder with the same appearance and taste as the experimental group orally. There were 10 people in each group. The skin moisture content of the five groups of volunteers was measured three times before taking the oral preparations, and the average value was taken as the baseline data. After the test started, the test groups 1 to 2 and the control group took a 5g dose of collagen composition and glucose powder orally once a day, respectively. Subsequently, at the start of the test The volunteers were tested at the 1st, 2nd, 4th, 6th and 8th week after use. The volunteers' daily drinking, exercise and other behaviors were recorded to ensure that the living habits of the two groups were consistent. The Corneometer instrument was used to test their skin moisture content. The measurements were repeated 3 times at the designated measurement points on the face and arms, and the average value was taken as the skin moisture content of the part. Each measurement was carried out in a constant temperature and humidity environment with a temperature of 22°C and a humidity of 60%. Volunteers needed to adapt to the environment in the measurement room for 30 minutes before the test to ensure that the skin condition was stable; and the moisture retention was calculated = (moisture content after use - moisture content before use) / moisture content before use × 100%. The results are as follows: Figure 4 shown.

[0116] Depend on Figure 4 As can be seen from the results, the collagen composition prepared by the present invention shows a significant moisturizing effect in improving skin moisture content, which is much better than the moisturizing performance of comparative example 1 and the control group; from the moisturizing performance fluctuation results of the control group, it can be seen that the skin moisture content of the control group fluctuates within ±3%, without a significant upward or downward trend, and the fluctuation amplitude is small, which is within the normal physiological range and will not have a significant impact on the reliability of the experimental results; from the results of comparative example 1 and embodiment 2, it can be seen that the better moisturizing performance may be due to the higher specific surface area and activity of the magnetic nano-immobilized enzyme, the enzymatic hydrolysis efficiency is improved, and the molecular weight distribution of the generated collagen peptide is more uniform and the biological activity is higher. In addition, the synergistic nano-sizing and encapsulation technology improves the stability and bioavailability of the active ingredients, and further enhances the moisturizing effect.

[0117] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A collagen composition for brightening skin, characterized in that: The composition includes the following raw materials in parts by weight: 40-60 parts of fish collagen peptide, 2-5 parts of arbutin extract, 0.1-0.5 parts of black pepper extract, 3-6 parts of glutathione, 1-3 parts of ellagic acid, 1-2 parts of shea butter, 3-5 parts of antioxidants, 1-2 parts of squalane, 1-2 parts of ceramide, 0.5-1 part of sodium bicarbonate, 5-10 parts of β-cyclodextrin, 1-3 parts of lecithin, and 0.5-1 part of silicon dioxide; The specific preparation steps of the fish collagen peptide are as follows: ①: The fish skin is repeatedly cleaned, soaked in a NaOH solution, and then soaked in an acetate buffer solution of pH 3 overnight to obtain a pre-treated raw material; the pre-treated raw material is heated in a water bath, filtered, and a collagen solution is obtained; ②: Add the magnetic nano-immobilized enzyme to the collagen solution prepared in step ①, stir evenly, control the temperature, adjust the pH, and perform enzymatic hydrolysis. After the reaction is completed, quickly lower the temperature to 4°C, separate the magnetic nano-immobilized enzyme with a magnetic separator, filter with a filter membrane, centrifuge, ultrafilter, and freeze-dry to obtain fish collagen peptides; In step 1., the ratio of the amount of the fish skin, the NaOH solution and the acetate buffer is 1g:10mL:10mL; The specific preparation steps of the magnetic nano-immobilized enzyme are as follows: Ⅰ: Dispersing the modified nanocellulose in deionized water, dispersing it evenly by ultrasonic treatment, and obtaining a modified nanocellulose suspension; adding FeCl3·6H2O and FeCl2·4H2O into the deionized water, stirring and mixing evenly, and obtaining an iron salt mixed solution; II: In a nitrogen atmosphere, slowly add the iron salt mixed solution prepared in step I to the modified nanocellulose suspension prepared in step I, stir and mix evenly, heat to increase the temperature, slowly add ammonia water to adjust the pH, and then stir to react. After the reaction is completed, cool to room temperature, centrifuge, take the precipitate, wash with deionized water until the pH is neutral, and vacuum dry to constant weight to obtain magnetic nanofibers; III: adding collagenase and trypsin to a phosphate buffer at pH 7, stirring and mixing evenly to obtain an enzyme solution; adding the magnetic nanofibers prepared in step II to a glutaraldehyde solution, heating in a water bath to increase the temperature, stirring gently, and washing with a phosphate buffer to obtain activated magnetic nanofibers; IV: adding the activated magnetic nanofibers prepared in step III to the enzyme solution, adding trehalose, and gently stirring the reaction, then using a magnet to separate the magnetic nanofibers after the enzyme is immobilized, washing with phosphate buffer, and vacuum freeze-drying to constant weight to obtain magnetic nano-immobilized enzyme; The specific preparation steps of the modified nanocellulose are as follows: (1): Disperse nanocellulose in anhydrous ethanol and perform ultrasonic treatment to obtain a nanocellulose dispersion; slowly add APTES to the nanocellulose dispersion under a nitrogen atmosphere, add 1 M ammonia water, heat in a water bath and stir to react, centrifuge, wash with anhydrous ethanol, and dry to constant weight to obtain amino nanofibers; (2): Dissolve PEG-COOH in 50 wt% ethanol, stir to dissolve evenly, add EDC and NHS, stir to react, and obtain an activated PEG-COOH solution; Dispersing the aminated nanofibers prepared in step (1) in 0.1 M PBS buffer to obtain an aminated nanofiber solution; (3): slowly dropwise adding the activated PEG-COOH solution prepared in step (2) into the amino nanofiber solution, controlling the pH, stirring the reaction under ice bath, centrifuging, washing with ethanol, and drying to constant weight to obtain modified nanocellulose; In step I, the ratio of the amount of FeCl3·6H2O, FeCl2·4H2O and deionized water is 1.8-2g:1g:50-100mL; in step II, the volume ratio of the iron salt mixed solution and the modified nanocellulose suspension is 1:1-2; In step III, the ratio of the amount of collagenase, trypsin and phosphate buffer is 6 mg:4 mg:5 mL; the activity of collagenase is 1500 U / g; the activity of trypsin is 4500 U / g; in step IV, the ratio of the amount of activated magnetic nanofiber and enzyme solution is 1 g:100 mL; In step (2), the ratio of the amount of PEG-COOH, EDC, NHS and 50wt% ethanol is 20g:2-2.3g:1.3-1.4g:200mL; in step (3), the volume ratio of the activated PEG-COOH solution and the amino nanofiber solution is 1.5-2:2; The specific preparation steps of the collagen composition are as follows: S1: dissolving arbutin extract, glutathione, ellagic acid, antioxidants and black pepper extract in distilled water, stirring until completely dissolved, adjusting the pH to 6.5-7, and obtaining an aqueous phase; adding shea butter, squalane and ceramide to a 70wt% ethanol solution, heating the solution to 40°C in a water bath, stirring to completely dissolve, and then adding lecithin, continuing to stir to form a uniform oil phase; S2: slowly adding the oil phase prepared in step S1 to the water phase, controlling the temperature to 4°C in an ice bath, and stirring at 10000 rpm for 15 min to obtain a primary emulsion; subjecting the primary emulsion to ultrasonic treatment at 400 W for 20 min in an ice bath, and then subjecting the homogenizer to a cycle treatment at 800 bar pressure for 3 times to obtain a nanoemulsion; S3: adding β-cyclodextrin to the nanoemulsion prepared in step S2, stirring and reacting at room temperature for 2 hours, and then vacuum rotary evaporating at 40°C for 2-4 hours to obtain an embedded emulsion; treating the embedded emulsion with a spray dryer, setting the inlet temperature to 80°C and the outlet temperature to 40-50°C to obtain a nano-embedded powder; S4: Stir the nano-embedded powder prepared in step S3, fish collagen peptide, sodium bicarbonate and silicon dioxide for 30 minutes to mix evenly to obtain a collagen composition.

Citation Information

Patent Citations

  • Whitening and freckle removing composition and application thereof

    CN107397697A

  • Preparation method of marine organism antibacterial peptide

    CN115232850A

  • Method for preparing collagen peptide through countercurrent immobilized enzyme column enzymolysis

    CN117551186A

Cited By

  • A long-acting moisturizing anti-wrinkle and anti-stain collagen composition and its preparation method and application

    CN122828101A